Adoption of HR 5.0 in Private Organizations of Kathmandu Valley - K.C., Kusum (Janabhawana Research Journal, 2025)
This study examines the awareness in HR 5.0 and the factors affecting the adoption of HR 5.0 by private organizations in Kathmandu valley. This study employed explanatory research design. Decision-making theory approach was used to conduct research. Data was collected from primary source through the use of self-administered questionnaire to 403 HR professionals in private organizations of Kathmandu valley selected by using convenience sampling. The sample comprised HR professionals having years of experience in the HRM, having diverse age groups, genders, and organizational levels. Similarly, Structural Equation Modeling was used to examine the key factors impacting the adoption of HR 5.0 in private organizations. The study found that the majority of respondents were aware of HR 5.0 and its principles. It is concluded that competence and strategy are the significant factors to impact the adoption of HR 5.0 while digitization and strategy have negligible impact. Majority of HR professionals responded that they are willing to adopt HR 5.0. However, there are challenges to adopt HR 5.0 in the organizations due to lack of skilled manpower, high cost, poor management support, lack of digital knowledge and government policies. Addressing employees’ feedback, proper government policy and the efficient use of available technology can be the managerial solutions to cope the challenges of adopting HR 5.0 in the private organizations.